Ultrastructural and quantitative analysis of cellular elements in the periodontal ligament premolars - M. V. Khertek; S. V. Logvinov (Бюллетень сибирской медицины, 2011)
A calculation and ultrastructural analysis of cellular elements in the periodontal ligament premolars with different surfaces (medial, distal, buccal and palatal) and at different levels of the roots. It is shown that the biomechanical load on the morphology of the premolars periodontal changes throughout the root, depending on the location of zones of compression and tension. Content of cells in the periodontium depends on the surface and the level of the tooth root.